Acute changes in free and extracellular vesicle-associated circulating miRNAs and myokine profile in professional sky-runners during the Gran Sasso d’Italia vertical run - Faraldi, M.; Sansoni, V.; Perego, S.; Gomarasca, M.; Gerosa, L.; Ponzetti, M.; Rucci, N.; Banfi, G.; Lombardi, G. (Frontiers in Molecular Biosciences, 2022)
Modification of gene expression profile, a first step in adaptation to exercise, leads to changes in the level of those molecules associated with skeletal muscle activity and energy metabolism, e.g., myokines, as well as those involved in their transcriptional regulation, e.g., microRNA. This study was aimed to investigate the influence of strenuous exercise on circulating microRNAs and their possible association with myokines response. Pre-competition and post-competition plasma samples were collected from 14 male athletes participating in a vertical run (+1000 m gain, 3600 m length). Circulating total (t-miRNA) and extracellular vesicles-associated (EV-miRNA) miRNAs were extracted from pooled plasma. Nanoparticle tracking analysis was performed to investigate pre- and post-competition EV concentration and size distribution. A panel of 179 miRNAs was assayed by qPCR and analyzed by Exiqon GenEx v6 normalized on Global Mean. t-miRNA and EV-miRNAs whose level was ≥5-fold up- or down-regulated were validated in each single subject. Target prediction on MirWalk v3.0, Gene-Ontology and pathway enrichment analysis on Panther v17.0 were performed to define the potential biological role of the identified miRNAs. A panel of 14 myokines was assayed in each sample by a multiplex immunoassay. In whole plasma, 5 miRNAs were upregulated and 2 miRNAs were downregulated; in the EV fraction, 5 miRNAs were upregulated and 3 miRNAs were downregulated. Nanoparticle tracking analysis revealed a similar EV size distribution in pre- and post-competition samples and a decreased concentration in post-competition samples related to pre-competition samples. Gene-Ontology and pathway enrichment analysis revealed that the identified t-miRNAs and EV-miRNAs were potentially involved in metabolism regulation in response to exercise. Correlation between fold-change of post-competition relative to pre-competition plasma level of both t-miRNAs and EV-miRNAs and myokines further confirm these results. This study provides an example of the systemic response to acute endurance exercise, in wich circulating miRNAs play a pivotal role.